Analisis Semantik dan Penggunaan Media Canva pada Pembuatan Slogan di Kelas VIII SMP Darussalam Medan - Qaqa Mahmudinejaz; Tri Indah Kusumawati; Budiman Budiman (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This research is entitled "Semantic Analysis and Use of Canva Media in Making Slogans in Class VIII of Darussalam Middle School, Medan". This research examines semantic analysis and the use of Canva media in the process of creating slogans by class VIII students at Darussalam Middle School, Medan. The main aim is to reveal the semantic meaning of the slogans produced by students. This research uses a descriptive method with a semantic approach, referring to Verhaar's semantic model, which involves analysis of lexical, grammatical and conceptual meaning. The research found three types of slogans created by students, namely health/hygiene slogans, education slogans, and motivation/advice slogans, each consisting of five slogans. Canva media has proven to be effective in helping students integrate visual and verbal elements, thereby increasing their creativity and understanding of the meaning of the slogans produced. Apart from that, using Canva also increases students' enthusiasm for learning through more interesting visual interactions. This research suggests that canva be used as a tool in teaching Indonesian, especially in material related to making slogans and understanding semantics. Lexical meaning analysis is carried out based on the meaning of words in the KBBI, grammatical meaning is analyzed through a morphophonemic process, and conceptual meaning is evaluated according to the relevant context